2011
DOI: 10.1146/annurev-bioeng-071910-124721
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Cardiovascular Strain and Intrinsic Wave Imaging

Abstract: Cardiovascular disease remains the primary killer worldwide. The heart, essentially an electrically driven mechanical pump, alters its mechanical and electrical properties to compensate for loss of normal mechanical and electrical function. The same adjustment also is performed in the vessels, which constantly adapt their properties to accommodate mechanical and geometrical changes related to aging or disease. Real-time, quantitative assessment of cardiac contractility, conduction, and vascular function before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 136 publications
(156 reference statements)
1
10
0
Order By: Relevance
“…These parameters are consistent with the kernel sizes and dimensions previously reported for strain imaging in 2-D (Konofagou et al, 2011; Korukonda and Doyley, 2011; Wang et al, 2008) and 3-D displacement estimation (Byram et al, 2010; Kuo and von Ramm, 2008). …”
Section: Methodssupporting
confidence: 90%
“…These parameters are consistent with the kernel sizes and dimensions previously reported for strain imaging in 2-D (Konofagou et al, 2011; Korukonda and Doyley, 2011; Wang et al, 2008) and 3-D displacement estimation (Byram et al, 2010; Kuo and von Ramm, 2008). …”
Section: Methodssupporting
confidence: 90%
“…Kanai has made measurements of the waves present in the heart as it beats (Kanai 2005; Kanai 2009). A method called electromechanical imaging has been used to measure the electromechanical waves propagating in the heart wall and the pulse waves propagating in the arterial vasculature (Pernot et al 2007; Wang et al 2008; Vappou et al 2010; Konofagou et al 2011; Provost et al 2011). A method that uses passive tomography methods, adapted from the field of seismology, has been reported that uses physiological motion to measure the shear wave velocity in various soft tissues (Benech et al 2009; Gallot et al 2011).…”
Section: Acoustic Wave Imaging Methodsmentioning
confidence: 99%
“…Lee et al have shown that RF-based speckle tracking provides accurate strain measurements when compared to tagged MR in 2D myocardial slices [12], [13]. They went on to show that 2D RF-based speckle tracking could be used to identify regions of abnormal cardiac function [14]. …”
Section: Introductionmentioning
confidence: 99%